Homeophasic Adaptation in Response to UVA Radiation in Pseudomonas aeruginosa: Changes of Membrane Fatty Acid Composition and Induction of desA and desB Expression - Pezzoni, Magdalena (2022)
In bacteria, exposure to changes in environmental conditions can alter membrane fluidity, thereby affecting its essential functions in cell physiology. To adapt to these changes, bacteria maintain appropriate fluidity by varying the composition of the fatty acids of membrane phospholipids, a phenomenon known as homeophasic adaptation. In Pseudomonas aeruginosa, this response is achieved mainly by two mechanisms of fatty acid desaturation: the FabA–FabB and DesA–DesB systems. This study analyzed the effect of ultraviolet-A (UVA) radiation—the major fraction of solar UV radiation reaching the Earth's surface—on the homeophasic process. The prototypical strain PAO1 was grown under sublethal UVA doses or in the dark, and the profiles of membrane fatty acids were compared at early logarithmic, logarithmic and stationary growth phases. In the logarithmic growth phase, it was observed that growth under sublethal UVA doses induced the expression of the desaturase-encoding genes desA and desB and increased the proportion of unsaturated fatty acids; in addition, membrane fluidity could also increase, as suggested by the indices used as indicators of this parameter. The opposite effect was observed in the stationary growth phase. These results demonstrate the relevant role of UVA on the homeophasic response at transcriptional level.